Evaluación de cuatro densidades de siembra de los Pastos Tanner (Brachiaria arrecta) y Janeiro (Eriochloa polystachya) para la producción bovina en la zona baja inundable de Babahoyo - Cepeda Alarcón, Luis Guillermo (2016)
VIII. SUMMARY This research was conducted at the Faculty of Agricultural Sciences at the Technical University of Babahoyo, located at Km 7 ½ of the way Babahoyo - Montalvo. The objective was to evaluate the four planting densities Tanner (Brachiaria arrecta) and Janeiro (Eriochloa polystachya) for bovine production in the lower floodplain pastures Babahoyo. Tanner grass was acquired from Livestock Experimental Farm campus of San Pablo belonging to the Faculty of Agricultural Sciences at the Technical University of Babahoyo and grass Janeiro obtained from the surrounding farming areas. The treatments were Factor A Tanner and grass varieties Janeiro and Factor (B) planting distances 0.40 x 0.80; 0.50 x 0.50; 0.70 x 0.40 and 0.80 x 0.80 m, giving a total of eight treatments and three replicates, which were compared by Tukey test at 95% probability. Crop development for analytical work and soil preparation, planting, weed control, fertilization, irrigation, plant protection and harvesting took place. In the present research work took the data of plant height at 90 and 120 days, length of the blade at 90 and 120 days entrenudo diameter of the lower middle third at 90 and 120 days, stem weight to 90 and 120 days, days to flowering, green weight and dry matter and economic analysis By the presented results it was determined that the evaluation of four grass planting densities showed good agronomic performance Janeiro for cattle production in the flood zone Babahoyo low; the tallest plants grass Janeiro (E. polystachya) a planting distance of 0.40 x 0.80 m stood at 90 and 120 days; Janeiro grass planting distance of 0.50 x 0.50 m obtained greater blade length and diameter of internode at 90 and 120 days; the two grass species flourished with an average of 30.4 days; the weight of the stem, green matter and dry matter, achieved better results in the planting of grass Janeiro distance of 0.80 x 0.80 m and the highest net benefit was observed in planting grass Janeiro distance of 0.80 x 0.80 m, with $ 817.12 / ha.